Clinical value of different QRS-T angle expressions. Issue 8 (13th September 2017) - Hnatkova, Katerina; Seegers, Joachim; Barthel, Petra; Novotny, Tomas; Smetana, Peter; Zabel, Markus; Schmidt, Georg; Malik, Marek
Abstract: Aims: Increased spatial angle between QRS complex and T wave loop orientations has repeatedly been shown to predict cardiac risk. However, there is no consensus on the methods for the calculation of the angle. This study compared the reproducibility and predictive power of three most common ways of QRS-T angle assessment. Methods and results: Electrocardiograms of 352 healthy subjects, 941 survivors of acute myocardial infarction (MI), and 605 patients recorded prior to the implantation of automatic defibrillator [implantable cardioverter defibrillator (ICD)] were used to obtain QRS-T angle measurements by the maximum R to T (MRT), area R to T (ART), and total cosine R to T (TCRT) methods. The results were compared in terms of physiologic reproducibility and power to predict mortality in the cardiac patients during 5-year follow-up. Maximum R to T results were significantly less reproducible compared to the other two methods. Among both survivors of acute MI and ICD recipients, TCRT method was statistically significantly more powerful in predicting mortality during follow-up. Among the acute MI survivors, increased spatial QRS-T angle (TCRT assessment) was particularly powerful in predicting sudden cardiac death with the area under the receiver operator characteristic of 78% (90% confidence interval 63–90%). Among the ICD recipients, TCRT also predicted mortality significantly among patients with prolonged QRS complex duration when the spatial orientation of the QRS complex is poorly defined. Conclusion: The TCRT method for the assessment of spatial QRS-T angle appears to offer important advantages in comparison to other methods of measurement. This approach should be included in future clinical studies of the QRS-T angle. The TCRT method might also be a reasonable candidate for the standardization of the QRS-T angle assessment.